To solve the equation \(2x - 5 = 3(4x + 5)\), let's outline the steps in order and fill in the necessary information.
Step 1: Distributive Property
Start by applying the distributive property on the right side of the equation:
\[ 2x - 5 = 3(4x + 5) \]
This becomes:
\[ 2x - 5 = 12x + 15 \]
Step 2: Combine Like Terms
Next, we want to get all the terms involving \(x\) on one side and constant terms on the other. We can subtract \(12x\) from both sides:
\[ 2x - 12x - 5 = 15 \]
This simplifies to:
\[ -10x - 5 = 15 \]
Step 3: Isolate the Variable
Now, add \(5\) to both sides to isolate the term with \(x\):
\[ -10x = 15 + 5 \]
This simplifies to:
\[ -10x = 20 \]
Step 4: Solve for the Variable
Finally, divide by \(-10\) to solve for \(x\):
\[ x = \frac{20}{-10} \]
This gives:
\[ x = -2 \]
So to summarize, here are the ordered steps for solving the equation:
- Distributive Property: Expand the equation to get \(2x - 5 = 12x + 15\).
- Combine Like Terms: Rearrange the equation to get \(-10x - 5 = 15\).
- Isolate the Variable: Add \(5\) to both sides to obtain \(-10x = 20\).
- Solve for the Variable: Divide by \(-10\) to find \(x = -2\).